The art of theatrical sound design a practical guide - Deiorio, Victoria (Backstage, 2019)
Emphasising the artistry behind the decisions made by theatrical sound designers, this guide is for anyone seeking to understand the nature of sound and how to apply it to the stage. Through tried-and-tested advice and lessons in practical application, The Art of Theatrical Sound Design allows developing artists to apply psychology, physiology, sociology, anthropology and all aspects of sound phenomenology to theatrical sound design. Structured in three parts, the book explores, theoretically, how human beings perceive the vibration of sound; offers exercises to develop support for storytelling by creating an emotional journey for the audience; considers how to collaborate and communicate as a theatre artist; and discusses how to create a cohesive sound design for the stage.